A computer system for continuous long-term recording, processing, and analysis of physiological data of brain injured patients in ICU settings. - Kropyvnytskyy I; Saunders F; Schierek P; Pols M (Brain Injury, 2001)
The objective of this project was to assemble and test a computer-based system for continuous long-term physiological data acquisition. The system would be used to study short-term (heart rate variability) and long-term (circadian rhythms) dynamics of physiological parameters in severely brain injured patients in ICU settings. A system has been built using open-source software and the Linux operating system as the platform. The system consists of three main parts: data acquisition, processing and analysis. The system was tested in ICU and experimental settings for long periods of time (up to 10 days of non-stop recording). The system appeared to function properly and accurately. Samples of the data according to the stages of acquisition-analysis process are presented in the paper. Avenues for the system use and development are discussed.